2018
DOI: 10.1038/s41467-018-04768-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of mouse models of human diseases via ABE- and BE-mediated base editing

Abstract: A recently developed adenine base editor (ABE) efficiently converts A to G and is potentially useful for clinical applications. However, its precision and efficiency in vivo remains to be addressed. Here we achieve A-to-G conversion in vivo at frequencies up to 100% by microinjection of ABE mRNA together with sgRNAs. We then generate mouse models harboring clinically relevant mutations at Ar and Hoxd13, which recapitulates respective clinical defects. Furthermore, we achieve both C-to-T and A-to-G base editing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 25 publications
2
111
0
Order By: Relevance
“…6 and Supplementary Table 3). As a result, we found no noticeable off-target sites likewise to the previous ABE-based gene editing studies 24,25,26 , suggesting potential clinical utility.…”
Section: Crispr-pass Rescues the Function Of Xpc Gene In Patient-derisupporting
confidence: 76%
See 1 more Smart Citation
“…6 and Supplementary Table 3). As a result, we found no noticeable off-target sites likewise to the previous ABE-based gene editing studies 24,25,26 , suggesting potential clinical utility.…”
Section: Crispr-pass Rescues the Function Of Xpc Gene In Patient-derisupporting
confidence: 76%
“…In this aspect, CRISPR-pass has important safety advantages relative to approaches that do rely on DNA cleavage. Furthermore, recent off-target profiling experiments on ABEs supported the high specificity of ABEs 24,25,26 , increasing the potential clinical utility of it. These characteristics suggest that CRISPR-pass might be useful for gene rescue in a clinical setting, as an alternative to existing drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the base editing windows for ABEs and CBEs at some target sites in our study (Table ) are larger than previously defined in mammalian systems (Gaudelli et al ., ; Komor et al ., ). Two recent in vivo base editing studies in mouse and rabbit also showed that ABEs and CBEs with SpCas9 can edit target adenines and cytosines outside of the canonical base editing activity windows at some target sites (Liu et al ., ,b). As the base editing windows characterized in previous studies were derived from limited target sites and were mainly from cell‐based assays which had relatively a short time for base editors to function (Gaudelli et al ., ; Komor et al ., ), more target sites need to be tested, and in vivo base editing studies are required to accurately define the base editing windows for both adenine and cytosine base editors.…”
Section: Resultsmentioning
confidence: 99%
“…While exceptional precision is paramount in a quest to correct somatic and in particular germline mutations, recent studies have revealed that CBEs can induce bystander mutations, including deletions, in mouse zygotes (5) and plants (6). In contrast, ABE displays a greater fidelity (5,7).…”
Section: Introductionmentioning
confidence: 99%
“…Since BE3 can introduce unwanted indels (1,5) and other undesirable base substitutions in addition to C-to-T conversions (5,7,11), the fourth-generation BE4, containing a second uracil glycosylase inhibitor (UGI) domain and optimized linker architectures, appears to have an increased fidelity in vitro (12), in mouse zygotes (5) and in rabbit embryos (13).…”
Section: Introductionmentioning
confidence: 99%